Maximum velocity sprint training: a case study investigating eccentric hamstring strength, fascicle length and force, velocity, and power profiling in semi-professional australian football - Freeman, B.; Talpey, S.; James, L.; Opar, D.; Young, W. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Sprint training is viewed as important for hamstring strain injury (HSI) prevention in Australian Rules Football (AF). Eccentric hamstring strength and biceps femoris long head (BFLH) fascicle length are modifiable risk factors for HSI. Maximum velocity sprint training has been viewed as less important than acceleration training for AF. Analysis of the influence of maximum velocity sprinting on force production and work completed shows a significant increase between 80% and 100% of maximum velocity. Therefore, maximum velocity training may provide a conditioning stimulus to the hamstrings that is not replicated in other training methods.